Study on the Dynamic Parameters of Plantar Pressure Applicable to the Elderly Screened by Delphi Method - YAN Yifeng; OU Jianlin; ZHENG Jiaxing; SUN Chenming; SHANG Yaru; CHEN Zhuoming (康复学报)
ObjectiveTo screen the plantar pressure dynamic parameters applicable to the elderly population, and to provide comparable parameters for the future scientific research.MethodsThe Delphi method was conducted. A research team was set up to design a questionnaire, and 25 medical experts in related fields were invited to complete the questionnaire survey and opinions were consulted on the commonly using parameters of plantar pressure dynamics sorted out by the research team. The positive coefficient, authority coefficient, coordination coefficient and each index score were calcula-ted. The final index screening criteria were "the arithmetic mean of total score ≥ the P25 of the arithmetic mean" or "the full score ratio of total score ≥ P25 of full score ratio" and "coefficient of variation of total score ≤ P75 of the coefficient of variation".ResultsThe 24 of 25 experts were actively involved in the initial consultation, and none of these experts reported being unfamiliar with the indicators. The average positive coefficient of experts in the two rounds of correspondence (96.00% in the first round and 91.67% in the second round) was as high as 93.84%, the authority coefficient was (0.728±0.373), and the opinion coordination coefficient was about 0.15 (all P<0.01). After screening, the dynamic parameters of plantar pressure applicable to the elderly were forefoot-to-rear foot plantar pressure ratio, asymmetry index, contact area, the time to peak pressure, load rate, intensity of peak pressure, intensity of pressure time integral, stress load, peak pressure, pressure time integral, full width at half maximum, average pressure (area), center of plantar pressure (COP).ConclusionThe dynamic parameters of plantar pressure selected for the elderly based on Delphi method are scientific and reliable. In this study, parameters suitable for the study of the elderly were screened out from numerous dynamic parameters, providing a relatively standardized reference range, which will make relevant scientific research more standardized and systematic and provide a reliable theoretical basis and reference for the studies of plantar pressure of the elderly in the future.